2010
DOI: 10.1039/b921384h
|View full text |Cite
|
Sign up to set email alerts
|

Excited state properties of aryl carotenoids

Abstract: Excited-state properties of aryl carotenoids, important components of light harvesting antennae of green sulfur bacteria, have been studied by femtosecond transient absorption spectroscopy. To explore effects of the conjugated aryl group, we have studied a series of aryl carotenoids with conjugated phi-ring, chlorobactene, beta-isorenieratene and isorenieratene, and compared them with their non-aryl counterparts gamma-carotene and beta-carotene, which contain beta-ring. Changing beta-ring to phi-ring did not r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 41 publications
5
36
0
Order By: Relevance
“…Therefore, there must be a reason other than light harvesting for these bacteria to synthesize carotenoids with the -ring. It has been suggested that the -interaction between the planar conjugated systems of the -ring and the BChl chlorin is responsible for the close contact between the two molecules (34). Since BChl-BChl -stacking plays an important role in stabilization of the aggregate (35), it is likely that the same is true for BChl-carotenoid interactions in chlorosomes from Chlorobi species.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Therefore, there must be a reason other than light harvesting for these bacteria to synthesize carotenoids with the -ring. It has been suggested that the -interaction between the planar conjugated systems of the -ring and the BChl chlorin is responsible for the close contact between the two molecules (34). Since BChl-BChl -stacking plays an important role in stabilization of the aggregate (35), it is likely that the same is true for BChl-carotenoid interactions in chlorosomes from Chlorobi species.…”
Section: Discussionmentioning
confidence: 82%
“…6). The conjugated system of the -ring is effectively disconnected from the conjugated system of the carotenoid backbone, and therefore, it does not alter the spectral coverage of the carotenoid absorption in the visible region compared to their precursors (␥-carotene and ␤-carotene) in their biosynthetic pathway (34). Therefore, there must be a reason other than light harvesting for these bacteria to synthesize carotenoids with the -ring.…”
Section: Discussionmentioning
confidence: 99%
“…Both molecules present an absorption band from 430 nm to 550 nm, with vibronic structures which are associated with the two b-end groups for b-carotene and with the keto carbonyl group for b-apo-8 0 -carotenal. [45][46][47] The vibrational progressions exhibit peaks separated by 155 meV in both molecules. Moreover, these compounds are completely transparent in the region above 590 nm.…”
Section: B Computational Detailsmentioning
confidence: 99%
“…This was proposed to arise from a decrease in orbital overlap between the p-orbital of the ring double bond and those of the polyene chain, as steric hindrance results in twisting of the conjugated end-cycles out of the conjugated plane [78]. Although the conjugated end-cycle contributes to the conjugation chain length [76,79], it extends it by the equivalent of only 0.3 of a C¼C bond. For instance, b-carotene, instead of showing the properties of a carotenoid with 11 C¼C bonds (as would be expected from its structure), presents the spectroscopic properties of a carotenoid with only 9.6 C¼C bonds [75,76].…”
mentioning
confidence: 99%